Innovation, Economic Growth, Internet Use and Domestic Credit in Asia and Oceania - Deddy Marciano; Viktor Adrian (UIN Raden Mas Said Surakarta, 2021)
Financial Development (FD) is part of a private sector development strategy to stimulate economic growth and reduce poverty, as well as address the